Understanding Risk of Suicide among perpetrators who view child sexual abuse material (CSAM). (July 2021) - Kothari, Radha; Key, Rebecca; Lawrenson, Jane; Squire, Tom; Farnham, Frank; Underwood, Alan
Abstract: Attempts to address the threat of harm posed by perpetrators of child sexual abuse (CSA) have rightly increased in recent years, with well-known efforts such as operation NOTARISE resulting in 750 arrests; however, the cost of such operations is also high. Operation NOTARISE resulted in 24 suicides; the estimated economic and social cost of which has been estimated to be £34.8 million. [1] Perpetrators who view child sexual abuse materials (CSAM) are not only at higher risk of suicide than the general population, individuals diagnosed with a mental health disorder, and perpetrators of other violent and sexual crimes, [2-5] but they also appear to be at higher risk of suicide than perpetrators of CSA who engage directly in sexual acts with a child . [6-8] An in-depth understanding of the experiences of CSAM offenders is missing in the literature, but is required to understand how to mitigate the risk of suicide amongst this high risk group. This qualitative study investigates the experiences of CSAM perpetrators from the perspectives of law enforcement officers (n = 16), CSAM perpetrators themselves (n = 5), and help-line operators who have provided support to CSAM perpetrators through the Lucy Faithfull Foundation "Stop it now!" helpline (n = 6). Analysis was conducted separately for each dataset and in accordance with guidelines set out by Braun and Clark . [9] The focus of this paper is the six over-arching themes that were common across all datasets: (i) offender demographics; (ii) psychological impact of arrest; (iii) coping with the investigation; (iv) cognitive distortion; (v) shame and stigma; and (vi) professional support. Findings are discussed in the context of the challenges faced by law enforcement and healthcare professions when providing support to this high risk group, and eight key recommendations are made to reduce the risk of suicide. Highlights: Risk of suicide is paricularly high among CSAM offenders. Critical periods of risk are arrest, bail, charge and sentencing. Confronting the reality and consequences of offences at arrest results in symptoms akin to trauma and adjustment disorder. Law enforcement support was viewed positively, mental health services had mixed views and social services were viewed poorly. Stigma associated with CSAM offences contributes to shame and self-hatred which increases risk and prevents help-seeking. Increased and more effective support is required at critical periods to reduce suicide risk and prior to this to reduce offending.